Implementation Of Green Grass Jelly To Reduce Blood Pressure In Hypertension Patients At Pasar Ikan Health Center, Bengkulu City, 2025 - Nurmareta, Della; Arfianti , Mariza; Aprianti, Delta (Multidisciplinary Journals, 2025)
Hypertension is a major global health problem, affecting approximately 1.28 billion people worldwide (WHO, 2024). In Indonesia, the prevalence of hypertension reached 34.1% in 2023, indicating a significant public health concern. At Pasar Ikan Health Center in Bengkulu City, hypertension cases have shown a marked increase, rising from 1,193 cases in 2020 to 2,307 cases in 2024. If left uncontrolled, hypertension can result in severe complications, including stroke, heart failure, and other cardiovascular diseases. Non-pharmacological interventions, such as the administration of green grass jelly, have been explored as complementary therapies to help manage blood pressure naturally. This study aimed to assess the effectiveness of green grass jelly in reducing blood pressure among hypertensive patients in the working area of Pasar Ikan Health Center, Bengkulu City, in 2025. A descriptive case study was conducted on one hypertensive patient who received 100 grams of green grass jelly daily for seven consecutive days. The patient’s blood pressure decreased from 140/90 mmHg before the intervention to 134/80 mmHg on the seventh day, indicating a positive response. These results suggest that green grass jelly is effective in helping to stabilize blood pressure. Therefore, it can be considered a safe, natural, and accessible complementary therapy for managing hypertension”